1992
DOI: 10.1093/bja/68.3.248
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Emptying During Lumbar Extradural Analgesia in Labour: Effect of Fentanyl Supplementation

Abstract: We measured gastric emptying (by paracetamol absorption) and duration of analgesia in 30 women in labour after extradural injection of 0.375% bupivacaine 10 ml either alone or combined with fentanyl 100 micrograms. Treatment was administered double blind by random allocation after the first request for analgesia. The median (range) times to maximal serum concentration of paracetamol were 60 (15-90) min and 75 (30-180) min after administration in the control and fentanyl groups, respectively (P = 0.026), and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…These physiological changes are less 48 h after delivery. [78][79][80] Continuous epidural infusion of lowdose local anaesthetic with fentanyl does not appear to delay gastric emptying until the total dose of fentanyl exceeds 100 mg. 68 Gastric emptying is not delayed in either obese or nonobese parturients at term who ingest 300 ml water after an overnight fast. 75 Pregnancy does not significantly alter the rate of gastric emptying.…”
Section: Effects Of Pregnancy On Gastric Functionmentioning
confidence: 99%
“…These physiological changes are less 48 h after delivery. [78][79][80] Continuous epidural infusion of lowdose local anaesthetic with fentanyl does not appear to delay gastric emptying until the total dose of fentanyl exceeds 100 mg. 68 Gastric emptying is not delayed in either obese or nonobese parturients at term who ingest 300 ml water after an overnight fast. 75 Pregnancy does not significantly alter the rate of gastric emptying.…”
Section: Effects Of Pregnancy On Gastric Functionmentioning
confidence: 99%
“…Rectal administration was chosen to eliminate the variable absorption associated with oral administration, the inevitable result not only of delayed gastric emptying and maternal emesis during labor 16 but also delayed gastric emptying when epidural analgesia contains fentanyl. 17 While rectal absorption of acetaminophen can also be variable, rectal absorption of acetaminophen in pregnancy may be improved secondary to increased pelvic blood flow. Although the effective serum doses for the treatment of pyrexia have been well studied, less is known about the use of acetaminophen prophylactically to prevent pyrexia.…”
Section: Commentmentioning
confidence: 99%
“…The authors noted that an empty stomach was not visible on ultrasound and admitted that including women with presumably empty stomachs would have yielded dramatically different results: "nearly" 30% compared with "nearly" two thirds having detectable food in the stomach (exact numbers were not reported). However, subsequent research has found that epidural opioids may delay gastric emptying (Ewah et al, 1993;Wright, Allen, Moore, & Donnelly, 1992). Whether or not epidural opioids were used in the Carp et al study (1992) is not known.…”
Section: Gastric Emptying In Labormentioning
confidence: 99%